Roman Catholicism for the Common Good: Its Spiritual, Theological and Religious Provisions - Mahalakshmi, L. S. P. (University of jaffna, 2024)
The profound common good of One Human Family in One Common Home is the theme I see coming through the Roman Catholic theological, spiritual and religious provisions. The prayers of St Pope John XXIII for a Renewed Pentecost indeed seem to have been answered in the Catholic Charismatic Renewal Movement (hereinafter CCRM), which is largely a movement of the Holy Spirit. A brief description of the origin of the CCRM, theology of the CCRM, spirituality of the CCRM, the Catholic interpretation of the Baptism in the Holy Spirit (hereinafter BHS) and others shall all be discussed. The need and effect of the gifts, fruits and charisms of the Holy Spirit, which manifest due to the theosis of the fellowship with the Holy Spirit and the consequent relationship with Jesus Christ shall be articulated. The effects of the theosis from BHS and the unitive dimensions of the theosis in the Catholic Charismatic Renewal (hereinafter CCR) shall be elaborated upon. Theosis in the CCR as a Renewed Pentecost shall be detailed in and the consequent reversal of the effects of the Original Sin due to obedience to Jesus highlighted. With the theosis and the effects of the Original Sin reversed, the human becomes a very different person. Then the charismatically renewed Catholic Church is presented as a paradigm for the common good with inputs from the CCR; the valuable, relevant detailed Papal encyclicals Laudato Si on safekeep of creation and Fratelli Tutti on the interactions with all other humans, in time bringing about One Human Family in One Common Home. A few rudimentary points which can slowly and steadily influence the world are elaborated upon to bring about the worthiest common good.
Keywords: Catholic charismatic renewal movement; Theosis; Common Good